Nanosecond pulsed laser processing turns engineering metal alloys antireflective and superwicking. (June 2020) - Samanta, Avik; Wang, Qinghua; Singh, Gurjap; Shaw, Scott K.; Toor, Fatima; Ratner, Albert; Ding, Hongtao
Abstract: In this work, superwicking and antireflective properties are achieved on engineering metal surfaces by creating a surface pattern using a high energy nanosecond pulsed laser followed by a chemical immersion treatment. The high-energy nanosecond pulse laser scans the metal surface in air. Subsequently, the laser-textured surface is further treated by immersion in a 3-cyanopropyltricholosilane reagent. As a result of these two processes, microgrooves with micro- and nano-scale surface features are generated on the metal surface. Due to the created surface structure and favorable surface chemistry, water sprints uphill defying the gravity. The fast self-propelling movement of water is due to the supercapillary effect of the surface microchannel and the superhydrophilic surface nitrile group. The wicking effect on the processed surface follows the classical square root of time dependence. The processed surface shows good antireflective properties in the visible and infrared spectrum. Surface features, surface chemistry, wettability, surface reflectivity and wicking behavior are measured on AA6061 and Ti-6Al-4V specimens through Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectroscopy (XPS), contact angle goniometer, UV-VIS-NIR spectrometer and high-speed camera, respectively.